Review on fluid structure interaction solution method for biomechanical application - Zakaria, Nazri Huzaimi (Trans Tech Publications Inc, 2014)
Fluid-Structure Interaction engages with complex geometry especially in biomechanical problem. In order to solve critical case studies such as cardiovascular diseases, we need the structure to be flexible and interact with the surrounding fluids. Thus, to simulate such systems, we have to consider both fluid and structure two-way interactions. An extra attention is needed to develop FSI algorithm in biomechanic problem, namely the algorithm to solve the governing equations, the coupling between the fluid and structural parameter and finally the algorithm for solving the grid connectivity. In this article, we will review essential works that have been done in FSI for biomechanic. Works on Navier–Stokes equations as the basis of the fluid solver and the equation of motion together with the finite element methods for the structure solver are thoroughly discussed. Important issues on the interface between structure and fluid solvers, discretised via Arbitrary Lagrangian–Eulerian grid are also pointed out. The aim is to provide a crystal clear understanding on how to develop an efficient algorithm to solve biomechanical Fluid-Structure Interaction problems in a matrix based programming platform.